Spiritual Care Education for Enhancing Clinical Competence, Confidence, and Caring Attitude: Mixmethod Study - Puspita Dewi, Inggriane; Wilandika, Angga; Aisyah, Popy Siti; Seman, Nordianna (Universitas Pendidikan Indonesia, 2025)
Introduction. Spiritual care is a vital component of nursing that meets patients' spiritual needs, particularly in palliative care. However, spiritual care education should be included in nursing curricula, especially in culturally diverse settings like Indonesia.Objective. This study aimed to evaluate the effectiveness of spiritual care education on nursing students' clinical competence, self-confidence, and caring attitudes during a four-week clinical rotation in a palliative care unit in Indonesia.Methods. A sequential explanatory design was used, combining quantitative and qualitative approaches. The quantitative phase involved 127 nursing students in a quasi-experimental design to assess changes in competencies. Data collection included questionnaires measuring self-efficacy, caring attitudes, clinical competency, and clinical judgment. The qualitative phase involved focus group discussions with ten purposively selected students to explore experiences and challenges in providing spiritual care. Quantitative data were analyzed using the Wilcoxon test, while qualitative data were analyzed through thematic analysis.Results. Quantitative findings significantly improved students' self-efficacy, caring attitudes, and clinical competence. Qualitative results revealed barriers to spiritual care, including communication difficulties, fear of errors, and cultural sensitivity.Conclusion. Integrating spiritual care into nursing education enhances nursing students' competence and caring attitudes. Addressing cultural and communication barriers is crucial for improving holistic patient care in diverse contexts